Sizing of Fuel Distribution and Thermopropulsion Systems for Liquid-Hydrogen-Powered Aircraft Using an MBSE Approach - Abdoulaye Sarr; Joël Jézégou; Pierre de Saqui-Sannes (Aerospace)
Hydrogen-powered aircraft constitute a transformative innovation in aviation, motivated by the imperative for sustainable and environmentally friendly transportation solutions. This paper aims to concentrate on the design of hydrogen powertrains employing a system approach to propose representative design models for distribution and propulsion systems. Initially, the requirements for powertrain design are formalized, and a use-case-driven analysis is conducted to determine the functional and physical architectures. Subsequently, for each component pertinent to preliminary design, an analytical model is proposed for multidisciplinary analysis and optimization for powertrain sizing. A double-wall pipe model, incorporating foam and vacuum multi-layer insulation, was developed. The internal and outer pipes sizing were performed in accordance with standards for hydrogen piping design. Valves sizing is also considered in the present study, following current standards and using data available in the literature. Furthermore, models for booster pumps to compensate pressure drop and high-pressure pumps to elevate pressure at the combustion chamber entrance are proposed. Heat exchanger and evaporator models are also included and connected to a burning hydrogen engine in the sizing process. An optimal liner pipe diameter was identified, which minimizes distribution systems weight. We also expect a reduction in engine length and weight while maintaining equivalent thrust.